Regulatory tensions in de facto unions and the promotion of marriage: a perceptual study in Peru (Research, Society and Development, 2020)
De facto unions have increased in Peru and currently enjoy legislative momentum. This situation is registered despite the legal support that the Peruvian state grants to marriage. The purpose of the article is to explore perceptions on the legal regulations of de facto unions and the violation of the constitutional duty of the state to promote marriage. 100 lawyers in free practice assigned to the Superior Court of Justice of the Department of La Libertad were consulted. The survey and a questionnaire (α: 0.825) were used. The average and standard deviation by indicator and dimension were obtained. To know the relationship between the dimensions, the Pearson correlation test (α: 0.05) was used. The dimension factors that limit the constitutional duty to promote marriage registers significant relationships with respect to: the Legal Nature of de facto unions (r: 0.571; p-value: 0.00); Principles of law that support the de facto union (r: 0.805; p-value: 0.00); Mechanisms of recognition of de facto unions (r: 0.729; p-value: 0.00) and Rights recognized to de facto unions (r: 0.642; p-value: 0.00). The perception of the regulation of de facto unions is positive, although it is considered that there is a violation of the constitutional duty to promote marriage. It is recommended to promote a constitutional modification that recognizes de facto unions as a figure that facilitates the strengthening, protection and family stability.